The Effect of Transformational Leadership, Workload, and Compensation on Employee Performance - Raharjo, Dwi Sihono; Widayati, C. Catur; Purnama, Eka Desy; Siahaan, C. Yohana (Advances in Social Sciences Research Journal, 2022)
This study aims to analyze the effect of transformational leadership, workload, and compensation on employee performance. The population is employees of the Branchless Banking division of PT Bank ABC in Indonesia with a saturated sample of 58 respondents. Collecting data using a survey method with a questionnaire based on a Likert Scale. The data analysis technique used is Component or Variance Based Structural Equation Model (SEM) where the data processing uses Partial Least Square (Smart-PLS). The results showed that (1) transformational leadership has a positive and significant effect on employee performance, (2) workload has a negative and significant effect on employee performance, (3) compensation has a positive and significant effect on employee performance. The implication of the hypothesis shows that there is an effect of transformational leadership, workload, and compensation together on employee performance with a variation of the effect of 93% while the rest is explained by other exogenous variables not studied.